Synergistic effect of hydrophilic nanoparticles and anionic surfactant on the stability and viscoelastic properties of oil in water (o/w) emulations; application for enhanced oil recovery (EOR) - Al-Anssari, Sarmad; Arain, Zain-UL-Abedin; Shanshool, Haider Abbas; Keshavarz, Alireza; Sarmadivaleh, Mohammad (Journal of Petroleum Research and Studies, 2020)
With the rapidly increased global energy demand, great attention has been focused on utilizing nanotechnology and particularly nanofluids in enhanced oil recovery (EOR) to produce more oil from low-productivity oil reservoirs. Nanofluid flooding has introduced as one of the promising methods for enhanced oil recovery using environment-friendly nanoparticles (NPs) to be as an innovative-alternative for chemical methods of EOR. This work investigates the synergistic effects of anionic surfactant and hydrophilic silica nanoparticles on the stability and the mechanical behavior of oil in water (O/W) emulsions for their application in EOR. To achieve this, an extensive series of experiments were conducted at a wide range of temperatures (23 – 70 °C) and ambient pressure to systematically evaluate the stability and the viscoelastic properties of the oil in water (O/W) emulsion with the presence of hydrophilic silica nanoparticles and an anionic surfactant. In this context, the initial oil to water volume ratio was 25:75. Sodium dodecylsulfate (SDS) was used as the anionic surfactant and n-decane was used as model oil. A wide concentration ranges of NPs (0.01 – 0.2 wt%) and surfactant (0.1 – 0.3 wt%) were used to formulate different emulsions. For stability measurements, a dynamic light scattering and zetasizer were used to measure the particle size distribution and zeta potential respectively. Creaming and phase behaviors were also investigated. The viscoelastic measurements were conducted using Discovery Hybrid Rheometer. Results show that in the presence of surfactant, and NPs mitigates the coalescence of dispersed oil droplets giving high promises in EOR applications. Further, over the tested range of temperatures, the viscosity of O/W emulsion remains stable which indicates thermal stability. Despite studies examining the use of nanoparticle-surfactant combination in sub-surface applications, no reported data is currently available, to the best of our knowledge, about the potential synergistic effect of this combination on the stability and viscoelastic properties of O/W emulsion. This study gives the first insight on nanoparticle-surfactant synergistic effect on oil in water (O/W) emulsion for EOR applications.